The Men of 1924: Britain's First Labour GovernmentThe Wild Men: The Remarkable Story of Britain's First Labour Government. - Catterall, Pippa (Parliamentary History, 2024)
The article discusses the formation and challenges faced by Britain's first Labour government in 1924. Led by Ramsay MacDonald, the minority government had to navigate a post-war economic environment with only 191 MPs. The government's achievements, such as the Housing Act and international diplomacy, were overshadowed by controversies, including handling domestic unrest and the fallout from a supposed letter from Zinoviev. Despite some solid accomplishments, the government ultimately fell to defeat in the general election due to tactical mistakes and external pressures.